Level of Public Knowledge Regarding Dental Radiographic Examination in Medan Perjuangan District - Trelia Boel; Dwina Pratiwi Harahap (Jurnal Syntax Admiration, 2024)
Aids in establishing the diagnosis, radiography also plays an important role in determining treatment plans and evaluating the results of treatment that has been carried out previously. The purpose of this study is to find out the extent of the level of knowledge of the community in Medan Perjuangan District regarding dental radiography. The type of research used is descriptive survey research with a cross sectional approach. The population of this study is the community in Medan Perjuangan District. The sample size is 200 people who meet the inclusion and exclusion criteria. By using questionnaires and analyzed descriptively. The result of this study is that the level of public knowledge regarding the uses, benefits, effects and dose limits as well as radiation protection of dental radiography obtained very few results that can be answered correctly. The satisfaction of this study is that the level of public knowledge in Medan Perjuangan District regarding dental radiography examinations individually obtained results in the good category of 2.0%, the fair category of 14.0%, and the poor category of 84.0%.